Keyword Searchable Public Key Encryption based on KPABE a Generic Approach - S. Ramana Priya,; GVS. Ananthanath, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In multi-user environments, implementing multi-keyword searchable systems comes with several major challenges—hiding both the search and access patterns, as well as defending against keyword guessing attacks (KGA). We have proposed a revolutionary new searchable encryption scheme that addresses all issues simultaneously. It renders the scheme very convenient for distribution in distributed systems. The scheme supports multi keyword searches. on encrypted data within a multi-writer and multi-reader framework, all while preserving the confidentiality of both the data and the search behavior.
Keywords: Searchable Encryption; Multi-Keyword Search; Multi-User Access; Search Pattern; Access Pattern